Penentuan Aktivitas Antikanker Fraksi Etil Asetat Daun Bandotan (ageratum conyzoides linn.) Terhadap Cell Line Kanker Kolon WiDr - lusiantika, linda; Widowati, Esti Wahyu; Adihimawati, Miranda (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2019)
A research to test the anticancer activity of in vitro anticancer activity against colon cancer cell line WiDr Ageratum conyzoides Linn.leafs. The aims of this study are to determine anticancer activity using MTT method. The method used is the extraction of secondary metabolites using maceration with n-hexane, ethyl acetate and ethanol, followed by TLC. Crude extract maceration results that have the highest yield selected and separated by fractions using KKV. Fractions with the greatest weight was chosen to be tested anticancer activity against WiDr cell line by MTT assay. Phytochemical screening and identification of compounds by GC-MS carried out on the fraction which has the lowest IC50 value. Maceration results showed that crude ethyl acetate extract had the highest amount of yield at 7.31% and has the best separation results of TLC is characterized by the highest number of stains. Separation by KKV produce 21 fractions, 4 fractions were selected based on the weight of the total of the fraction 6, 13, 14 and 15. Test anticancer activity with a concentration of 62.5; 125; 250; 500 and 1000 mg mL-1 shows the fraction 6 has the lowest IC50 value is 251.48 mg mL-1. Based on this, the fraction 6 does not have anticancer activity. Although, the phytochemical screening showed alkaloids and terpenoids as well as the result of identification with GC-MS indicated the presence of compounds 2H-benzopyran and neophytadiene Keywords: Ageratum conyzoides Linn. leaves, Column Cromatography Vacuum, anticancer, phytochemical, GC-MS